PENGARUH TEKNIK ROLE PLAYING UNTUK MENGATASI AGRESIF VERBAL SISWA MELALUI BIMBINGAN KELOMPOK DI SMPN 1 PEKANBARU - Agis Marisyah; Raja Arlizon; Donal Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to find out the aggressive verbal description of students before and after being given a Role Playing technique, students 'aggressive verbal differences before and after being given a Role Playing technique and to reduce students' aggressive verbal skills through group guidance. The research method used is a quantitative method with the type of pre-experimental one group pretest-posttest research. The subjects of this study were eighth grade students of Pekanbaru State Junior High 1 with aggressive verbal high, amounting to 7 people. The instruments of data collection used were questionnaires using a Likert scale. The data analysis technique used is the Non Parametric statistical technique using the Wilcoxon Test and the Spearman Rank Test. The results showed that aggressive verbal students before being given role playing techniques through group guidance were mostly in the high category at 14% and after being given role playing techniques through the guidance of verbal aggressive groups students experienced a decrease in the moderate category of 71, 42% and in the moderate category 28.57%. Based on the Wilcoxon Test there are significant differences in student self-confidence before and after being given role playing techniques through group guidance with a significance value of 0.018 <α 0.05. Based on the Spearman Rank Test, it can be concluded that the relationship between role playing techniques through group guidance and student confidence is in the high category of 0.793 or 62.8%. Next to find out the coefficient of determination as follows: (rs) 2 = (0.793) 2 = 0.628. This means that the influence of role playing techniques through group guidance services to increase student self-confidence is 62.8% while 37.2% is influenced by other factors that originate in students and from the student environment.Key Words: Role Playing Technique, Self Confidence, Group Guidance